A non-linear Black-Scholes equation. (2nd June 2009) - Qiu, Yan; Lorenz, Jens
We study a modification of the Black-Scholes equation allowing for uncertain volatility. The model leads to a partial differential equation with non-linear dependence upon the highest derivative. Under certain assumptions, we show existence and uniqueness of a solution to the Cauchy problem.